Rapid tumor shrinkage with lapatinib plus capecitabine in a patient with massive liver involvement. Issue 6 (November 2013) - Giotta, Francesco; Latorre, Agnese; Cramarossa, Antonio; Simone, Giovanni; Florio, Carlo; Oliva, Stefano; Lorusso, Vito
We present the case of a 58-year-old woman with breast cancer metastasizing to the liver after adjuvant chemotherapy. A liver biopsy confirmed metastatic lesions from breast cancer that were immunohistochemically positive for estrogen/progesterone receptors and HER2. After first-line treatment with trastuzumab and vinorelbine, the patient commenced therapy with capecitabine (1000 mg/m 2 twice daily, days 1–14) and lapatinib (1250 mg/day). Three months after the administration of this combination therapy, the liver metastases had shrunk substantially. Lapatinib may have the potential to convert trastuzumab-refractory tumors to trastuzumab-sensitive tumors in HER2-positive breast cancer by upregulation of the cell surface expression of HER2. Further study will be needed to evaluate in the clinic the combination of lapatinib and an m-TOR inhibitor as a treatment approach in HER2 overexpressing breast cancer that shows a poor response to trastuzumab.